THE IMPLEMENTATION OF FASTING FIDYAH ACCORDING TO IMAM SYAFIâ€™I IN PAYA GELI VILLAGE OF SUNGGAL DISTRICT DELI SERDANG - Arifin, Zainal; Aqsha, Muhammad; Fauzi Lubis, Muhammad (Universitas Dharmawangsa Medan, 2020)
But thereâ€™s a scripture deduction in Al- Baqarah (184) : Meaning : â€œAnd upon those who are able (to fast, but with hardship) a ransom ( as suitable) offeeding a poor person (each day).â€ This verse explained that Rukhsah was given byAllah for certain person. Study of fasting fidyah according to Imam Syafiâ€i are: (a)senile person cause Elderly; (b) a prolonged illness that canâ€™t possibly cure, (c).Pregnant and nursing woman who are worried for their children. (d) died person andhave a fasting load that wasnâ€™t on Qada in his lifetime.